THE ILLOCUTIONARY ACT OF ISLAMIC VIDEO ENTITLED “THE MEANING OF LIFE” BY TALK ISLAM - MUHAMMAD FATKHU ARIFIN; FITRI PALUPI (Sriwijaya University Learning and Education International Conference, 2016)
The title of this research is “The Illocutionary Act of Islamic Video Entitled „The Meaning of Life‟ by Talk Islam”. This research is purposed to answer the problem formulation that questioning about the types of the utterances, the functions of illocutionary acts, and the context of illocutionary act‟s functions.This research used descriptive qualitative method that described the data which have been collected. The object of this research is the illocutionary acts of the video entitled “The Meaning of Life” by Talk Islam. The data are collected by downloading the video through You Tube site. The collected data, then was analyzed by dividing the illocutionary acts into some types of utterance, they are; imperative, interrogative, and declarative. To find the context, the illocutionary acts are divided into some functions, those are; representative, directive, expressive, commisive, and declarative. Furthermore, The result shows that the speaker spoke mostly declarative utterances followed by interrogative utterances, and then imperative utterances. The speaker delivered most of his illocutionary acts with representative function, the following illocutionary acts are with expressive function, directive function, declarative function, and commisive function. Seeing the percentages, it shows that the speaker intended to provides the strong argument with the massive evidences sourced from the Holy Quran.